COVID-19 in Immunosuppressed Children - Nicastro, Emanuele; Verdoni, Lucio; Bettini, Laura Rachele; Zuin, Giovanna; Balduzzi, Adriana; Montini, Giovanni; Biondi, Andrea; D'Antiga, Lorenzo (Frontiers in Pediatrics, 2021)
Following the spread of the SARS-CoV-2 infection and coronavirus disease 2019 (COVID-19) to a global pandemic, concerns have arisen for the disease impact in at-risk populations, especially in immunocompromised hosts. On the other hand, clinical studies have clarified that the COVID-19 clinical burden is mostly due to over-inflammation and immune-mediated multiorgan injury. This has led to downsizing the role of immunosuppression as a determinant of outcome, and early reports confirm the hypothesis that patients undergoing immunosuppressive treatments do not have an increased risk of severe COVID-19 with respect to the general population. Intriguingly, SARS-CoV-2 natural reservoirs, such as bats and mice, have evolved mechanisms of tolerance involving selection of genes optimizing viral clearance through interferon type I and III responses and also dampening inflammasome response and cytokine expression. Children exhibit resistance to COVID-19 severe manifestations, and age-related features in innate and adaptive response possibly explaining this difference are discussed. A competent recognition by the innate immune system and controlled pro-inflammatory signaling seem to be the pillars of an effective response and the premise for pathogen clearance in SARS-CoV-2 infection. Immunosuppression—if not associated with other elements of fragility—do not represent per se an obstacle to this competent/tolerant phenotype in children. Several reports confirm that children receiving immunosuppressive medications have similar clinical involvement and outcomes as the pediatric general population, indicating that maintenance treatments should not be interrupted in suspect or confirmed SARS-CoV-2 infection.